The Epididymis as a Target for Toxicants - De Grava Kempinas, W. [UNESP]; Klinefelter, G. R. (Elsevier, 2017)
The epididymis is the organ in which sperm mature by developing the capacity for progressive motion and fertilizing ability. There is evidence that sperm quality in humans and other animals has diminished, in parallel with increased adverse trends in male reproductive health. It is speculated that these events may have manifested from environmental influences. Sperm maturation is a complex and poorly understood process, and sperm quality may also be compromised by acceleration of sperm transit time throughout the epididymal duct. Herein we will discuss epididymal toxicology, a relatively new facet of male reproductive toxicology.
Keywords: Androgen; Biomarker of fertility; Environmental contaminants; Epididymis; Male reproductive health; Reproductive development; Sperm maturation; Sperm quality; Sperm transit time; Toxicology